Does Lifestyle Affect Dysmenorrhea Intensity? A Cross-Sectional Study: Apakah Gaya Hidup Mempengaruhi Intensitas Dismenore? Sebuah Studi Cross-Sectional - Vetinly; Hernanto, Annisa D. P.; Polim, Arie A. (Indonesian Socety of Obstetrics and Gynecology, 2022)
Objective : To determine whether or not there is a relationship between lifestyle and dysmenorrhea intensity in FKIK Atma Jaya students. Methods : This research is a cross sectional analytic descriptive study with a minimum sample size of 196 students of the FKIK Atma Jaya class 2017-2019. The degree of pain was assessed using the Verbal Multidimensional Scoring System pain scale. Frequency of fast food consumption were assessed with Food Frequency Questionnaire. Frequency of physical activity were assessed with International Physical Activity Questionnaire. The datas were analyzed using the Kolmogorov-Smirnov normality test, the Mann-Whitney U test, and the Kruskal-Wallis test. Results : The highest percentage of menstrual pain was at grade 1 (painful menstruation; rarely disturbed activity; no systemic symptoms; rarely required analgesics) for the VMSS scale (46.3%). The percentage of fast food consumption in this study was 86.1%. The highest percentage of physical activity in the category of moderate physical activity was 56.2%. The results of this study indicates a significant relationship between consumption of fast food and the intensity of dysmenorrhea with p = 0.017. There were no significant relationship between physical activity and the intensity of dysmenorrhea with p = 0.225 Conclusion : Consumption of fast food were related to the intensity of dysmenorrhea, whereas physical activity was not related with the intensity of dysmenorrhea. Keywords : dysmenorrhea, , fast food consumption, lifestyle, physical activity Abstrak Tujuan : Untuk mengetahui ada tidaknya hubungan gaya hidup dengan intensitas dismenore pada mahasiswa FKIK Atma Jaya. Metode : Penelitian ini merupakan penelitian deskriptif analitik cross sectional dengan jumlah sampel minimal 196 mahasiswa FKIK Atma Jaya angkatan 2017-2019. Derajat nyeri dinilai dengan menggunakan skala nyeri Verbal Multidimensional Scoring System. Frekuensi konsumsi makanan cepat saji dinilai dengan Food Frequency Questionnaire. Frekuensi aktivitas fisik dinilai dengan International Physical Activity Questionnaire. Data dianalisis menggunakan uji normalitas Kolmogorov-Smirnov, uji Mann-Whitney U, dan uji Kruskal-Wallis. Hasil : Persentase nyeri haid tertinggi pada derajat 1 (nyeri haid; aktivitas jarang terganggu; tidak ada gejala sistemik; jarang memerlukan analgesik) untuk skala VMSS (46,3%). Persentase konsumsi fast food dalam penelitian ini adalah 86,1%. Persentase aktivitas fisik tertinggi pada kategori aktivitas fisik sedang adalah 56,2%. Hasil penelitian ini menunjukkan adanya hubungan yang signifikan antara konsumsi fast food dengan intensitas dismenore dengan p = 0,017. Tidak ada hubungan yang bermakna antara aktivitas fisik dengan intensitas dismenore dengan p=0,225 Kesimpulan : Konsumsi fast food berhubungan dengan intensitas dismenore, sedangkan aktivitas fisik tidak berhubungan dengan intensitas dismenore. Kata kunci : aktivitas fisik, dismenore, gaya hidup, konsumsi fast food